Dinamika Motivasi Belajar Peserta Didik pada Era Digital: Analisis Psikologis Berdasarkan Teori Motivasi Kontemporer - Rika Sri Wahyuni; Alfi Rahmi (Lembaga Yasin AlSys, 2026)
Students’ learning motivation in the digital era has become an important issue in educational psychology because changes in technology-based learning environments influence students’ engagement, independence, and self-regulation. Nevertheless, studies that integrate contemporary motivation theories to explain the dynamics of learning motivation in the context of digital learning remain limited. This study aims to analyze the dynamics of students’ learning motivation in the digital era through the perspective of educational psychology by examining the influence of digital learning environments, the interrelationship among motivational dimensions, and the need for adaptive learning strategies. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using thematic analysis. The findings show that learning motivation is influenced by the interaction among individual psychological factors, the characteristics of digital technology, and support from the social environment. Digital learning environments can increase learning flexibility and independence, but they also create distractions that may reduce motivation. In addition, autonomy, a sense of competence, social support, learning goal orientation, and self-regulation interact with one another in shaping students’ motivation. These findings affirm the importance of adaptive, interactive, and student-centered learning strategies to maintain learning motivation and engagement in digital learning. The conclusion of this study indicates that students’ learning motivation in the digital era is a multidimensional construct influenced simultaneously by psychological, technological, and social aspects. The implications of this study provide a theoretical contribution to the development of educational psychology studies through the integration of contemporary motivation theories, as well as a practical reference for educators and educational institutions in designing digital learning that is responsive to students’ needs.